PROBLEMATIKA EKSISTENSI KEPEMIMPINAN PEMERINTAHAN ADAT DI MALUKU - Muhtar Muhtar; Nur Hidayat Sardini; Fitriyah Fitriyah; Wahab Tuanaya (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2022)
The existence of traditional village government eroded during the New Order era with the implementation of Law No. 5 of 1979 which made village administration uniform throughout Indonesia including Maluku Province. In the reform era and after that, there was a shift in power from centralization to decentralization in the form of changes in regulations until the issuance of Law Number 6 of 2014 concerning Villages. The issuance of the Village Law has implications for the government's recognition and respect for the rights of traditional communities. However, this later became an obstacle to the birth of a definitive government in traditional villages/traditional villages in Maluku because it was related to the leadership problem of traditional village or customary land administration. The problem is related to the matarumah parentah or clan who has the right to lead the customary land as a King who is appointed through customary deliberations by the Negeri Saniri Institution. This problem is still a serious problem because it often creates horizontal conflicts. By using a qualitative-descriptive research method to answer how problematic the existence of traditional government leadership in Maluku Province is, the research results contain a number of findings. First, Matarumah Parentah is a symbiosis of customary inheritance. Second, there is a conflict of interest in the election and determination of the definitive head of government (king). Third, musyawarah negeri saniri becomes an arena of conflict of interest. Fourth, the existence of customary government can still be found in several places in Maluku, such as Buru District and the Kei Islands.